Improving Public Service Quality: Optimalization Strategies for Sub-District Government Office in Ambon City - Sahetapy, Petronela; Bahasoan, Aminah (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research focuses on optimizing public service quality provided by the Teluk Ambon Sub-District Government Office in Ambon City. A descriptive approach with qualitative and quantitative analysis techniques was utilized for the study. The study indicates that the uniform treatment of public service reporting is the most dominant factor affecting the optimization of public service quality. To achieve optimal public service quality, it is necessary to prioritize the strengthening and improvement of both qualitative and quantitative aspects of public service optimization at the Teluk Ambon Sub-District Government Office. The research findings have implications for improving public services in sub-district government offices by implementing prioritized qualitative and quantitative strategies to achieve optimal public service quality. The study proposes several strategies for improving public service quality in sub-district government offices, aiming to enhance the quality of public services provided.